Identification of Discovery Learning Method Based on Edutainment (Zenius) to Increase Student Motivation on Business and Energy Materials - Lika Anggraini; Feliza Paramitha Sinaga; Sri Wina Oktavia (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This research aims to identify the effectiveness of discovery learning methods based on edutainment, specifically using the Zenius application, to enhance student motivation in learning business and energy concepts. Methodology: This qualitative research employs a literature study approach, with sources obtained from books, journals, and other relevant materials. Data analysis was conducted using the Miles and Huberman model. Main Findings: The literature study revealed that the edutainment-based discovery learning method, exemplified by the Zenius application, significantly enhances students’ understanding of business and energy topics. This research aims to provide readers with valuable insights into the benefits of edutainment-based discovery learning methods like Zenius. Novelty/Originality of this study: This study contributes new knowledge by demonstrating the potential of edutainment-based discovery learning methods to improve student engagement and comprehension in business and energy subjects. It advances existing knowledge by highlighting the practical application of the Zenius platform in educational settings, offering a novel approach to integrating technology and learning.